THU0363 Efficacy and Tolerability of Anti-TNF Therapies in Patients with Non-Radiographic Axial Spondyloarthritis: An Observational Cohort Study from Southern Sweden. (23rd January 2014) - Kristensen, L.; Kapetanovic, M.; Saxne, T.; Gulfe, A.; Geborek, P.
Abstract : Background: Treatment recommendations for patients with axial spondyloarthritis (SpA) [1 ], including non-radiographic axial SpA (nr-axSpA), presents anti-TNF therapies as an option in patients who fail NSAIDs, however at present clinical data targeting nr-axSpA has been sparse. Objectives: To evaluate the efficacy and tolerability of anti-TNF therapy in nr-axSpA patients treated in clinical practice. Methods: 112 patients with nr-axSpA and high disease activity as well as inadequate response or intolerance to NSAIDs receiving their first course of anti-TNF therapy were prospectively included in this cohort study. Patients fulfilling modified New York criteria for ankylosing spondylitis were excluded. 89% (N=99) of the included patients fulfilled ASAS criteria for axial SpA. Results: At baseline median age was 38 years, 59% were males, 79% of the patients had imaging suggestive of sacroiliitis (primarily inflammation on MRI), 71% were HLA-B27 positive, and the median disease duration was 6 years and 10 months. At 6 months of follow-up the median BASDAI decreased from 5.6 to 3.2 (p=0.002), BASFI decreased from 3.9 to 1.8 (p=0.005), and CRP 4.4 mg/L to 1.7 mg/L (p=0.001). After 1 year of treatment the mean drug survival was 75%, and at 2 years of follow-up this fraction decreased to 64%. Patients with positive MRI findings at baseline had significantly better drug survival (HR=0.33 CI 0.16-0.69; p=0.002). Also male sex was associated with higher drug survival (HR=0.45 CI 0.24-0.85; p=0.011). CRP-level at baseline was not associated with drug survival. Image/graph: Conclusions: Anti-TNF treatment of patients with nr-axSpA in clinical practice resulted in effective control of disease activity and good drug survival. Results from this study suggest that male gender and positive MRI findings at baseline are associated with a favourable treatment course. References: van der Heijde D et al. ASAS recommendations for axSpA. Ann Rheum Dis 2011;70:905–8. Disclosure of Interest: L. Kristensen Consultant for: Pfizer, Wyeth, Abbott, BMS, MSD, M. Kapetanovic: None Declared, T. Saxne: None Declared, A. Gulfe: None Declared, P. Geborek: None Declared